Manuscritos dos séculos XVIII e XIX : edições semidiplomáticas e notas ortográficas - Paula, Ana Maria Alves Rodrigues de (2012)
This research consists of paleographic analysis of handwritten documents dated from the eighteenth and nineteenth centuries. Those documents belongs to the Public Archives of Mato Grosso. Those were presented in facsimile and semidiplomatic with justalinear presentation to facilitate comparison between the editions, followed by a survey of spelling aspects of writing presented in the folios studied, in order to understand the language used in Mato Grosso, in the period, for spelling, according to the concepts of philology and textual criticism, contributing to the formation of Brazilian Portuguese language.